2020
DOI: 10.3390/v12040399
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Cytoplasmic Aggregates and Inclusions Are Critical Cellular Regulatory and Antiviral Factors

Abstract: RNA granules, aggresomes, and autophagy are key players in the immune response to viral infections. They provide countermeasures that regulate translation and proteostasis in order to rewire cell signaling, prevent viral interference, and maintain cellular homeostasis. The formation of cellular aggregates and inclusions is one of the strategies to minimize viral infections and virus-induced cell damage and to promote cellular survival. However, viruses have developed several strategies to interfere with these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 108 publications
(126 reference statements)
0
28
0
Order By: Relevance
“…Recent work on coxsackievirus A16 revealed that SGs induced early during infection were later cleared by autophagy as a means to suppress antiviral immune signaling [380]. Some viruses hijack the autophagic degradation pathway or use autophagosome-derived compartments to support their replication [381,382]. Infectious bursal disease virus is an example of a virus that subverts the autolysosome for virus assembly and maturation in an acidic environment [383].…”
Section: Granulophagymentioning
confidence: 99%
“…Recent work on coxsackievirus A16 revealed that SGs induced early during infection were later cleared by autophagy as a means to suppress antiviral immune signaling [380]. Some viruses hijack the autophagic degradation pathway or use autophagosome-derived compartments to support their replication [381,382]. Infectious bursal disease virus is an example of a virus that subverts the autolysosome for virus assembly and maturation in an acidic environment [383].…”
Section: Granulophagymentioning
confidence: 99%
“…I propose that APOLs, PI4KB and PHB participate in the formation of autophagosomes induced by type I interferon‐mediated inflammation [145] (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetical involvement of APOLs in the formation of autophagosomes induced by type I interferon. Aggresomes are virus‐induced aggregates that become enclosed in autophagic structures to limit infection and favour cell recovery [145], but such structures may be used by some viruses for their replication [131,147]. APOLs could control the initiation of isolation membranes by Golgi‐derived vesicles, owing to their effect on PI(4)P synthesis by PI4KB [8], which is key to autophagy initiation [56,166].…”
Section: Apols and Viral Infectionmentioning
confidence: 99%
See 2 more Smart Citations